1991
DOI: 10.1111/j.1476-5381.1991.tb12220.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of thromboxane A2 (TP‐) receptors: evidence from antagonist but not agonist potency measurements

Abstract: 1 Thromboxane A2 (TP-) receptors in human, rat and rabbit platelets and in smooth muscle of guineapig trachea, rat aorta and rabbit aorta have been characterized by measurement of the potencies of agonists and antagonists having considerable variations in chemical structure. 2 On each washed platelet system, eight prostanoids induced maximal irreversible aggregation (full agonists) and the potency ranking was EP 171 > STA2 > 9,11-azo PGH2 > 9,11-endoxy-lOa-homo PGH2 > U-46619 (standard) > PGH2 = 16-p-fluorophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…We have recently reported low affinities for several TP-receptor antagonists (e.g. EP 092, EP 169 and ONO 11120) on two other rabbit isolated preparations, the thoracic aorta ring and blood platelets (Tymkewycz et al, 1991). In early experiments on the jugular vein it was found that none of the three antagonists showed greater blocking potency than GR 32191 (unpublished observations).…”
Section: Discussionmentioning
confidence: 97%
“…We have recently reported low affinities for several TP-receptor antagonists (e.g. EP 092, EP 169 and ONO 11120) on two other rabbit isolated preparations, the thoracic aorta ring and blood platelets (Tymkewycz et al, 1991). In early experiments on the jugular vein it was found that none of the three antagonists showed greater blocking potency than GR 32191 (unpublished observations).…”
Section: Discussionmentioning
confidence: 97%
“…With higher affinity TP antagonists in human and rat platelet assays, surmountability is seen for the shapechange response, whereas insurmountability occurs for aggregation. This profile is still compatible with a reversible-competitive mechanism, because slow dissociation of the high-affinity antagonist from the TP receptor retards agonist (U-46619) occupancy in the early stage of the aggregation response, thereby favoring the disaggregation process and insurmountability; in contrast, the nonfading shape-change response affords a truer measure of dose ratios at steady state (Armstrong et al, 1985;Jones et al, 1989;Lumley et al, 1989;Tymkewycz et al, 1991;Ogletree et al, 1993).…”
mentioning
confidence: 99%
“…There has been much debate about the existence of different TP receptor subtypes in platelet and vascular smooth systems (Mais et al, 1985(Mais et al, , 1988Swayne et al, 1988;Morinelli et al, 1989;Masuda et al, 1991;Tymkewycz et al, 1991;Folger et al, 1992). It is certainly clear that species heterology exists; for example, higher affinities are often found for human and rat platelet TP receptors compared with rabbit platelet TP receptors (Tymkewycz et al, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…U46619 is a stable and full ago nist analogue of thromboxane A2 (17,18). Recently, the human thromboxane A2 receptor was cloned, and its amino-acid sequence shows that it is one of the G protein coupled receptors (19).…”
Section: Discussionmentioning
confidence: 99%